Pembentukan Karakter Perilaku Sosial Siswa di Era Revolusi Industri 4.0 pada Generasi Z dalam Pembelajaran IPS Kelas VIII MTs Al Ma’arif Tulungagung - Nur Alvi Puriamandawati; Jani Jani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The industrial revolution 4.0 requires elementary and secondary education institutions to improve, even evaluate the learning system of each field of study taught. Around 30% of the world's population has used social media in order to connect, seek information and learn. The same is true for the development of social studies education which continues to experience changes in materials or learning activities that are in accordance with the conditions of students and their environment. The focus of the research in this thesis is: (1) How is the formation of social behavioral character of students in social studies learning of class VIII MTs Al Ma'arif Tulungagung in the era of the Industrial Revolution 4.0 in Generation Z?, (2) What are the supporting and inhibiting factors in the formation of social behavioral character of class VIII MTs Al Ma'Arif Tulungagung students in social studies learning in the era of the Industrial Revolution 4.0 in Generation Z, (3) What are the positive and negative impacts of the Industrial Revolution 4.0 era on the formation of social behavioral character of class VIII MTs Al Ma'arif Tulungagung students in social studies learning in Generation Z?. This study aims to examine the formation of students' social behavior through social studies learning, as well as the factors that influence and the impact of the Industrial Revolution 4.0 era on class VIII students of MTs Al Ma'arif Tulungagung. This research approach uses a qualitative method known as an artistic method because the data produced is in the form of interpretations of data findings in the field. Furthermore, the type of research used is descriptive qualitative research by collecting accurate data by going directly to the field by utilizing the method of answering and describing a phenomenon that is the focus of the research. The results of the study concluded that: (1) Social studies learning at MTs Al Ma'arif Tulungagung forms students' social behavior through the values ​​of empathy, responsibility, and communication, (2) This character formation is supported by technology, the role of the family, and the school environment, but is hampered by the negative influence of social media and the tendency of Generation Z to seek instant solutions. (3) The Industrial Revolution 4.0 has a positive impact on access to information and critical thinking, but also has negative impacts such as gadget dependence and cyberbullying.